Efficacy of the teachers committee meetings based on teachers’ views - Hasan DEMİRTAŞ; Mehmet ÜSTÜNER; Niyazi ÖZER; Melike CÖMERT (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
This study intends to determine the efficacy of teachers’ committee meetings, based on the views of high school teachers. To realize this aim, “Teachers Committee Meeting Evaluation Scale”, developed by the researchers, was given to a total of 276 high school teachers, (F=105, M=171). According to the results, it was found that the teachers evaluated these meetings moderately effective. It was also found that teachers’ views did not differ significantly in terms of gender, teaching field, service duration, school type, and work year in current school. However, they were significantly different in terms of teacher population in the school. In another words, as teacher population in a school increases, the efficacy of the meetings tend to decrease.